2004
DOI: 10.1097/00005537-200407000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Restoring Vocal Fold Movement after Transection and Immediate Suturing of the Recurrent Laryngeal Nerve with Local Application of Basic Fibroblast Growth Factor: An Experimental Study in the Rat

Abstract: bFGF facilitates regeneration of the transected RLN and attenuation of intrinsic laryngeal muscle atrophy, thereby restoring laryngeal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…Muscle fibre size is therefore a useful parameter to record the effect of growth factors. Both basic fibroblast growth factor (Motoyoshi et al ., 2004) and insulin‐like growth factor (Shiotani et al ., 1998) have been shown to enhance the cross‐sectional area of the TA muscle following RLN transection. However, we found that NT‐3 had no overall effect on PCA muscle fibre size, possibly because the NT‐3 enhanced axonal growth was not translated into sufficiently increased muscle reinnervation or the muscle fibres were reinnervated by an ‘incorrect’ neuronal type.…”
Section: Discussionmentioning
confidence: 99%
“…Muscle fibre size is therefore a useful parameter to record the effect of growth factors. Both basic fibroblast growth factor (Motoyoshi et al ., 2004) and insulin‐like growth factor (Shiotani et al ., 1998) have been shown to enhance the cross‐sectional area of the TA muscle following RLN transection. However, we found that NT‐3 had no overall effect on PCA muscle fibre size, possibly because the NT‐3 enhanced axonal growth was not translated into sufficiently increased muscle reinnervation or the muscle fibres were reinnervated by an ‘incorrect’ neuronal type.…”
Section: Discussionmentioning
confidence: 99%
“…To quantify the glottal area, the glottal images with full abduction and adduction captured by PhotoImpact were dragged into the worksheet of the PhotoShop (Adobe, San Jose, CA). After the free edges of the vocal folds in each image were traced (24), the number of pixels encompassed by the vocal fold edges was then displayed in the histogram dialog box. Changes in the glottal area during respiratory cycle and in response to intravenous administration of capsaicin could be calculated by comparing the number of pixels encompassed by a reference area taken simultaneously with the images.…”
Section: Methodsmentioning
confidence: 99%
“…Studies examining the use of growth factors on denervation-related TA atrophy have shown promising results and have highlighted the importance of studying these factors in relation to agerelated atrophy. [195][196][197][198] According to the World Health Organization, those over 60 years of age are making up an everincreasing segment of the world population. 199 Although this realization clearly touts the societal and medical advances of recent years, it also offers considerable challenges to those providing care for this population.…”
Section: Future Directionsmentioning
confidence: 99%